“Chinary” in M. Kuzmin’s Journals - Andrei B. Ustinov (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2021)
The paper presents selected records from Mikhail Kuzmin’s diary that deal with – directly or indirectly – Daniil Kharms and his literary associates since the first mentioning of “mystic-futurist Vvedensky” on March 16, 1924, and up to the arrest of Kharms and Vvedensky in “Gosizdat Juvenile Sector case” in December 1931. The records reveal lots of new biographical facts and aspects of literary life of the time. The publication is provided with the necessary commentary and the introductory article that recreates the background of Kuzmin’s relations with “Chinary” and later with OBERIU in the context of Leningrad culture of the late 1920s-early 1930s. A special attention is paid to the writers of “Kuzmin circle” that had personal relationships with Vvedensky and Kharms.